Farmer’s Club - Jena, Siddhartha Swarup; Jena, Nandita (Indian Farming, 2017)
For transmitting the latest agriculture techniques to the Farmers’ field, orienting them to establish better relationship with banks, adoption of latest post-harvest handling technology, value addition, etc. and enjoy the benefits of collective bargaining power both for procuring inputs and selecting their produce, the Farmers’ Club Programme is an appropriate and most suitable strategy initiated by NABARD in 1982.